2012
DOI: 10.1186/1743-7075-9-50
|View full text |Cite
|
Sign up to set email alerts
|

Monosodium glutamate (MSG) intake is associated with the prevalence of metabolic syndrome in a rural Thai population

Abstract: BackgroundEpidemiology and animal models suggest that dietary monosodium glutamate (MSG) may contribute to the onset of obesity and the metabolic syndrome.MethodsFamilies (n = 324) from a rural area of Thailand were selected and provided MSG as the sole source for the use in meal preparation for 10 days. Three hundred forty-nine subjects aged 35–55 years completed the study and were evaluated for energy and nutrient intake, physical activity, and tobacco smoking. The prevalence of overweight and obesity (BMI ≥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 23 publications
3
89
0
2
Order By: Relevance
“…Furthermore, ACTH will stimulate the adrenal glands to produce cortisol. Cortisol caused fat breakdown in adipose tissue and increased levels of triglycerides and free fatty acids in the blood [12,13]. The results of in vitro experiment showed that cortisol increased lipoprotein lipase in adipose tissue and some part of visceral fat where lipolysis is activated.…”
Section: Resultsmentioning
confidence: 78%
“…Furthermore, ACTH will stimulate the adrenal glands to produce cortisol. Cortisol caused fat breakdown in adipose tissue and increased levels of triglycerides and free fatty acids in the blood [12,13]. The results of in vitro experiment showed that cortisol increased lipoprotein lipase in adipose tissue and some part of visceral fat where lipolysis is activated.…”
Section: Resultsmentioning
confidence: 78%
“…Monosodium glutamate is a worldwide used flavour enhancer with a level of consumption that has increased during the last two decades (Insawang et al, 2012). It can be used as purified glutamate salt or as a component of a mixture of amino acids and small peptides commonly called bouillon cube.…”
Section: Discussionmentioning
confidence: 99%
“…Глобальні зміни в способі життя людства, об-меження фізичної активності, зростання в раціоні ха-рчування рафінованих вуглеводів, жирів тваринного походження, хаотичний режим харчування, безконт-рольне використання харчових добавок, насамперед глутамату натрію, призводять до пандемії ожиріння, що характеризується надмірним накопиченням у жи-ровій тканині триацилгліцеролів [5,6].…”
Section: літературний оглядunclassified